Fabrication and evaluation of potentiometric sensors of an anticancer drug (Gemcitabine) - Al-Kashef, Iyad Darweesh; Saadeh, Salman Mostafa; Almonem, Khalid Ibrahim Abed; Ghalwa, Nasser Mohammed Abu; Shawish, Hazem Mohammed Abu (European Journal of Chemistry, 2020)
Accurate, rapid and inexpensive determination of gemcitabine, an anticancer drug, is of high interest. This manuscript describes the use of potentiometric sensors as a basis for this work given their known attractive characteristics that meet our needs. Potentiometric sensors were comprised of carbon paste S1, coated wire S2 and PVC membrane S3, of gemcitabine (an anticancer drug) were fabricated, studied and evaluated. The calibration plots for these electrodes showed a Nernstian slope of 58.4±0.3, 59.5±0.3 and 58.3±0.3 mV per decade with the limit of detection: 6.50×10-5, 7.20×10-5 and 4.60×10-5 for sensors S1, S2 and S3, respectively. The electrodes have a short and stable response time of ~5 seconds and good reproducibility in a pH range of 2.5-9.5. The present sensors show distinct selectivity toward the drug ion in comparison to several inorganic ions, sugars, amino acids and some common drug excipients. Gemcitabine was determined successfully in ampoules and urine using these sensors by the calibration curve method.